Uranium phytoremediation by Helianthus annuus L. and Amaranthus caudatus L. plants - Majid Mahdieh; Mohammedreza Sangi; Saeid Hamidi; Seyed M. Talebi; Alex V. Matsyura (Acta Biologica Sibirica)
Uranium contamination presents significant challenges to biological systems due to its chemical toxicity and radiological impacts. Rhizofiltration emerges as a cost-effective strategy for environmental remediation of uranium. This study aimed to compare the uranium uptake capabilities of two plant species, Helianthus annuus L. (sunflower) and Amaranthus caudatus L. (purple amaranth), in a hydroponic system. The plants were cultivated in nutrient solutions supplemented with 0.5 mM or 1 mM UO₂(NO₃)₂.6H₂O without phosphate. After 14 days of growth, we assessed uranium uptake. Our findings revealed that H. annuus effectively removed over 95% of the initial uranium concentration from the solution, while A. caudatus exhibited a removal efficiency of approximately 65–80%. In both species, uranium accumulation and transport to the upper, harvestable parts were limited. The highest uranium concentration was observed in the roots of H. annuus (37,050.8 ± 3,547 mg kg-1 DW), whereas A. caudatus roots had a noticeably lower concentration (14,944.68 ± 3,278 mg kg-1 DW). Interestingly, A. caudatus demonstrated greater uranium accumulation in its shoots compared to H. annuus. Overall, while H. annuus demonstrates superior potential for uranium rhizofiltration, A. caudatus emerges as a promising candidate as a hyperaccumulator for uranium.